Induced Genetic Variation in Crop Plants by Random or Targeted Mutagenesis: Convergence and Differences - Holme, Inger B.; Gregersen, Per L.; Brinch-Pedersen, Henrik (Frontiers in Plant Science, 2019)
New Breeding Techniques (NBTs) represent the newest technology for introduction of new variation into crop plants for plant breeding, in particular the methods that aim to make targeted mutagenesis at specific sites in the plant genome (NBT mutagenesis). In a decision from 2018, the EU Court of Justice deemed plants modified by these techniques to be GMO. The decision was based in a context of conventional plant breeding using mutagenesis of crop plants by physical or chemical treatments. These plants are explicitly exempted from the EU GMO regulation, based on the long-termed use of mutagenesis. In its decision, the EU Court claims that the NBTs operate “at a rate out of all proportion to those resulting from the application of conventional methods of mutagenesis”. In this paper, we argue that in fact this is not the case anymore; instead, a convergence has taken place between conventional mutagenesis and NBTs, in particular due to the possibilities of TILLING methods that allow the fast detection of mutations in any gene of a genome. Thus, by both strategies mutations in any gene across the genome can be obtained at a rather high speed. However, the differences between the strategies are 1) the precision of the exact site of mutation in a target gene, and 2) the number of off-target mutations affecting other genes than the target gene. Both aspects favour the NBT methods, which provide more precision and fewer off-target mutations. This is in stark contrast to the different status of the two technologies with respect to EU GMO regulation. In the future, this situation is not sustainable for the European plant breeding industry, since it is expected that restrictions on the use of NBTs will be weaker outside Europe. This calls for reconsiderations of the EU regulation of plants generated via NBTs.